Olfactomedin 4 as a novel loop of Henle‐specific acute kidney injury biomarker - Denise C. Hasson; Kelli Krallman; Katherine VanDenHeuvel; Shina Menon; Giovanna Piraino; Prasad Devarajan; Stuart L. Goldstein; Matthew N. Alder (Physiological Reports, 2022)
Abstract Acute kidney injury (AKI) is associated with morbidity and mortality. Urinary biomarkers may disentangle its clinical heterogeneity. Olfactomedin 4 (OLFM4) is a secreted glycoprotein expressed in stressed neutrophils and epithelial cells. In septic mice, OLFM4 expression localized to the kidney's loop of Henle (LOH) and was detectable in the urine. We hypothesized that urine OLFM4 (uOLFM4) will be increased in patients with AKI and sepsis. Urine from critically ill pediatric patients was obtained from a prospective study based on AKI and sepsis status. uOLFM4 was quantified with a Luminex immunoassay. AKI was defined by KDIGO severe criteria. Sepsis status was extracted from the medical record based on admission diagnosis. Immunofluorescence on pediatric kidney biopsies was performed with NKCC2, uromodulin and OLFM4 specific antibodies. Eight patients had no sepsis, no AKI; 7 had no sepsis but did have AKI; 10 had sepsis, no AKI; 11 had sepsis and AKI. Patients with AKI had increased uOLFM4 compared to no/stage 1 AKI (p = 0.044). Those with sepsis had increased uOLFM4 compared to no sepsis (p = 0.026). uOLFM4 and NGAL were correlated (r2 0.59, 95% CI 0.304–0.773, p = 0.002), but some patients had high uOLFM4 and low NGAL, and vice versa. Immunofluorescence on kidney biopsies demonstrated OLFM4 colocalization with NKCC2 and uromodulin, suggesting expression in the thick ascending LOH (TALH). We conclude that AKI and sepsis are associated with increased uOLFM4. uOLFM4 and NGAL correlated in many patients, but was poor in others, suggesting these markers may differentiate AKI subgroups. Given OLFM4 colocalization to human TALH, we propose OLFM4 may be a LOH‐specific AKI biomarker.